2015
DOI: 10.1155/2015/823620
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Regulator of Signaling Networks in Metastatic Colon Cancer

Abstract: MicroRNAs (miRNAs) are a class of small, noncoding RNA molecules capable of regulating gene expression translationally and/or transcriptionally. A large number of evidence have demonstrated that miRNAs have a functional role in both physiological and pathological processes by regulating the expression of their target genes. Recently, the functionalities of miRNAs in the initiation, progression, angiogenesis, metastasis, and chemoresistance of tumors have gained increasing attentions. Particularly, the alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 120 publications
0
55
0
Order By: Relevance
“…miRNAs play a key role in many crucial biological processes such as cell proliferation, differentiation, and apoptosis in colon cancer, and continued efforts will help identify new targets for the diagnosis, prognosis, and management of colon cancer [8, 16, 17]. Recently, miR-663a, which belongs to the primate specific miRNAs, was detected as a tumor suppressing miRNA in several cancer cells including colon cancer cells [18–20].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs play a key role in many crucial biological processes such as cell proliferation, differentiation, and apoptosis in colon cancer, and continued efforts will help identify new targets for the diagnosis, prognosis, and management of colon cancer [8, 16, 17]. Recently, miR-663a, which belongs to the primate specific miRNAs, was detected as a tumor suppressing miRNA in several cancer cells including colon cancer cells [18–20].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have revealed that a network of miRNAs is involve in the pathogenesis of CRC (Martín‐Subero & Esteller, ; Trang et al, ). Deregulation of these molecules could lead to inhibition and/or activation of several cellular and molecular targets that trigger development of CRC (Wang, Du, Liu, Cho, & Yang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the assessment of prognostic factors is pivotal for the management of unresectable colorectal cancer patients. Several underlying mechanisms have been described in the past decades, including multiple molecular alterations, which confer the tumorigenesis and progression of colorectal cancer [1318]. However, the exact underlying molecular markers for survival assessment of colorectal cancer remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%